SKILLS FOR ADOLESCENCE - SUSAN CARROLL KEISTER; APACKI CAROL, KAYE CATHRYN BEGER, BARR LINDA ETC. (LIONS QUEST IN INDIA FOUNDATION B-94 ''PARISEEMA" C. G. ROAD, AHMEDABAD -380006)
This book designed to fulfill these requirements and to respond to the changing world faced by young people and their families.
Keywords: CHILD AND ADOLESCENT DEVELOPMENT